A Política Nacional de Resíduos Sólidos e sua aplicação no município de Ribeirão Preto - SP: gestão e manejo dos resíduos sólidos domésticos urbanos - Ricco, Rubens Francisco (2014)
This work attempts to the problem of solid domestic urban waste (RSDU) in the city of Ribeirão Preto - SP, Brazil, and to the process of the ongoing implementation of the National Policy on Solid Waste (PNRS). Analyzes the development of international and national guidelines and laws relevant to the subject, and the formulation of the sectorial plan for urban sanitation and solid waste management of this city, its general issues and, especially, all your management system, handling and disposal the prediction of a Public Private Partnership (PPP). It also examined the problem of the current predominant form of management and planning in government and the PPP, also the current stage of capitalism that prioritizes private sectors participation in public affairs and the increasing production and consumption of goods. Another important point relates to the question of recycling and the collectors cooperatives of these materials, an important point of PNRS. The survey was developed through technical visits in all localities of the management and disposal of RSDU and cooperative of recyclable materials, interviews with agents of government, responsible for waste management, and agents of civil society who promoted, and are monitoring the process, ongoing approval of the sectorial plan for urban sanitation and solid waste management, as well as attempt of municipal government approving the PPP of waste. In this process occurred broad participation of civil society that could change and add several points in sectorial plan and suspended the PPP because of some irregularities founded. There are historical environmental liabilities arising from improper disposal of RSDU; agglutination of urban sanitation and solid waste management in a few companies, attempted adoption of a PPP services that would concentrate all these services in one company; and a selective collection of recyclable materials that has been poor and insignificant, and such service along with the inclusion of waste pickers and the cooperative are not clearly included in the sector plan, like the PNRS requires